Effect of dolomite and pig manure on growth and production of carrots (Daucus carota) - NOVITA DEWI SAMBI; YUSUF LIMBONGAN; ADEWIDAR M. PATA’DUNGAN (Smujo International, 2023)
Abstract. Sambi ND, Limbongan Y, Pata’dungan AM. 2023. Effect of dolomite and pig manure on growth and production of carrots (Daucus carota). Nusantara Bioscience 14: 22-29. This study aims to see how dolomite and pig manure affect carrot (Daucus carota L.) plant development and taproot production. The research was conducted from May to August 2021 in the Padangiring Village, Rantetayo Sub-district, Tana Toraja District, South Sulawesi, Indonesia. Three levels of dolomite in combination with four levels of pig manure were used: control (no treatment), and dolomite at 3 tons/ha, 6 tons/ha, and pig manure at control (no treatment), and 20 tons/ha, 30 tons/ha, and 40 tons/ha. The optimal dolomite level of 3 tons/ha significantly influenced plant height, the number of leaves, taproot length, and taproot diameter but had no significant effect on individual taproot weight, plot taproot weight, or taproot weight per hectare. The optimal pig manure dose of 4 kg/plot (40 tons/ha) showed a substantial influence on all investigated variables. The interaction between dolomite and pig manure substantially influenced taproot length but had no effect on the other observable variables. The optimum treatment combination was 3 tons/ha of dolomite with 40 tons/ha of pig manure, yielding 38.67 tons/ha of carrot taproots. Thus, commercial carrot growth and production may be boosted by a combination of dolomite and pig manure.